INFLUENCE OF TAURINE ON LARVAL EYE DEVELOPMENT AND GROWTH PERFORMANCE OF GOLDEN RABBITFISH (Siganus guttatus) - Darsiani Darsiani; Mia Setiawati; Dedi Jusadi; Muhammad Agus Suprayudi; Asda Laining (SEAMEO BIOTROP, 2024)
ARTICLE HIGLIGHTS- Taurine improves eye development in golden rabbitfish larvae- Enhanced growth performance with taurine-enriched rotifers- Taurine positively impacts fish eye and body growthABSTRACTGolden rabbitfish (Siganus guttatus) is an emerging species for aquaculture industry, despite constrains faced on commercial scale of seed production due to the high mortality during the first-feeding stage. An experiment was conducted to determine the effect of taurine through enrichment of rotifers as live-feed on eye development and growth performance of larval golden rabbitfish. Observation of eye development was carried out by measuring eye diameter of the larva and development of the retina based on histology assessment. Growth performance was measured for absolute growth and fin development of the larvae and survival rate. The results showed that taurine-enriched rotifer generally provided better performances for eye development and growth of larval golden rabbitfish compared with control (without taurine). Increase of taurine dose up to 0.050 g/L resulted in an increase of eye diameter, absolute growth, fin development and survival rate. Further increased increment of the taurine tended to decrease the values of the measured parameters. The eye diameter of larval golden rabbitfish fed with 0.050 g/L taurine-enriched rotifer was significantly wider (106.1±9.8 µm) (P < 0.05) compared with control (58.2±14.3 µm), but did not significantly differ from other doses of taurine (P > 0.05). Body width of larvae fed with 0.050 g/L taurine-enriched rotifer was significantly higher (127.3±14.6 µm) (P < 0.05) compared with control (98.8±18.3 µm). In regard to eye development, growth performances (total length, fin development and survival rate), dose of taurine for rotifer enrichment fed to larval golden rabbitfish Siganus guttatus was 0.050 g/L.